Open-loop speed control of permanent magnet synchronous motor fed by matrix converter - Kavuran, Gürkan; Orhan, Ahmet (My University, 2010)
Nowadays, permanent magnet synchronous motors (PMSM) are widely used in industrial applications due to their advantages such as, high efficiency, high power density and low inertia. Also PMSMs are suitable for pumps, fans, robots, industrial equipment and electrical vehicles. In this study, a MATLAB/SIMULINK© model for the openloop V/f speed control system of a three phase PMSM fed by a matrix converter is investigated. Venturini's modulation algorithm is used for the matrix converter's switches in the simulation model. Motor's performance has been examined for variable speeds and loads.
Matris çeviriciden beslenen sürekli miknatisli senkron motorun açik çevrim hiz kontrolü
2010 7th National Conference on Electrical, Electronics and Computer Engineering, ELECO 2010 -- 2 December 2010 through 5 December 2010 -- Bursa -- 83834
Keywords: AC generator motors; AC motors; Automobile electronic equipment; Electric vehicles; Electrical engineering; Industrial applications; Magnetic devices; Pumps; Synchronous motors; Electrical vehicles; High efficiency; High power density; Industrial equipment; MATLAB /simulink; Matrix converter; Open loops; Permanent Magnet Synchronous Motor; Permanent magnets